2017
DOI: 10.1007/s10661-017-6362-z
|View full text |Cite
|
Sign up to set email alerts
|

Consumption of heavy metal contaminated foods and associated risks in Bangladesh

Abstract: This study investigated the magnitude of heavy metal contamination and determined the carcinogenic as well as non-carcinogenic risks associated with selected food consumption in Bangladesh. Commonly consumed varieties of rice, vegetables, and fish samples were analyzed to measure the concentrations of heavy metals such as cadmium, chromium, lead, arsenic, manganese, nickel, and zinc. These staple food items showed the greatest probabilities of heavy metal contamination in different phases of their production a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
3

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 52 publications
(14 citation statements)
references
References 39 publications
0
11
3
Order By: Relevance
“…Market samples provide important insights into the average contamination levels of heavy metals and metalloids in foods in Bangladesh. Rice, fish, and vegetables from Kawran Bazar, Dhaka, were all found to contain Cd and Pb in higher concentrations than the safe limits [97]. In their market-based study, Shaheen et al [98] showed that mangos ( Mangifera indica ) presented excess Pb and tomatoes ( Solanum lycopersicum ) contained excess Cd.…”
Section: Crop Heavy Metal and Metalloid Pollutionmentioning
confidence: 99%
“…Market samples provide important insights into the average contamination levels of heavy metals and metalloids in foods in Bangladesh. Rice, fish, and vegetables from Kawran Bazar, Dhaka, were all found to contain Cd and Pb in higher concentrations than the safe limits [97]. In their market-based study, Shaheen et al [98] showed that mangos ( Mangifera indica ) presented excess Pb and tomatoes ( Solanum lycopersicum ) contained excess Cd.…”
Section: Crop Heavy Metal and Metalloid Pollutionmentioning
confidence: 99%
“…Its continuous exposure can cause degenerative diseases in the skeletal and nervous systems. Their alteration can be related to different conditions such as multiple sclerosis, Parkinson's disease, muscular dystrophy, Alzheimer's disease, and different cancer types [44]. The metal residues presence in the herbal plants is prevalent, since they are easily contaminated during growth, development, and processing [45].…”
Section: Table-3: Labeling Percentage Of the Analyzed Samples Of Eachmentioning
confidence: 99%
“…The maximum health threat assessments link human exposure to heavy metals in other sources such as water, air, newspapers, wall paints, furniture dust, toys and soil [1][2][3][4][5][36][37][38][39][40][41]. Experimental and epidemiological investigations have revealed a link between heavy metal exposure and cancer occurrence in animals and human beings [36,42,43]. The International Agency for Research on Cancer (IARC) and the World Health Organization have regulated and categorized them as probable human carcinogens [36,42,44,45].…”
Section: Introductionmentioning
confidence: 99%
“…Experimental and epidemiological investigations have revealed a link between heavy metal exposure and cancer occurrence in animals and human beings [36,42,43]. The International Agency for Research on Cancer (IARC) and the World Health Organization have regulated and categorized them as probable human carcinogens [36,42,44,45]. The German Federal Agency for Consumer Protection and Food Safety (GFACPFS) has issued the strictest guidelines relating to the presence of some heavy metals (Pb, As and Cd) in cosmetic products, where the levels must be 2, 0.5 and 0.1 µg/g, correspondingly [46].…”
Section: Introductionmentioning
confidence: 99%